ini Isim Fā’il dalam QS Al-Anfāl: Pola, Fungsi, dan Relevansi dalam Pembelajaran Ilmu Sharaf: Studi Linguistik Qur’ani Berbasis Analisis Morfologis dan Pendekatan Induktif - Ihsan Irfandi; Muhammad Sayuti; Moh. Abdul Kholiq Hasan (Language Development Center, 2025)
Background: Arabic morphology plays a crucial role in understanding the grammatical and semantic structure of the Qur’anic language. Purpose: This study aims to analyze the patterns, meanings, functions, and syntactic roles of ism fāʿil in Surah al-Anfāl and explore its implications for Arabic grammar instruction. Method: This research adopts a qualitative approach with a library research method. The primary data source is the Qur'anic text of Surah al-Anfāl, supported by classical linguistic commentaries. The study identifies and classifies ism fāʿil based on morphological patterns (wazn), analyzes their syntactic functions in the verses, and evaluates their grammatical activity (i.e., whether they act as verbs in raising objects). Furthermore, this study discusses how these findings can be adapted into Arabic teaching using an inductive approach. Results and Discussion: The study found 35 occurrences of ism fāʿil in six different morphological patterns, with فَاعِلٌ as the most frequent. Many forms perform grammatical actions similar to verbs. Most ism fāʿil function as mubtada’, khabar, or faʿil in nominal and verbal sentences. This study fills a gap in the literature by combining linguistic analysis with pedagogical application using inductive teaching models. Conclusions and Implications: The use of Qur’anic texts for teaching Arabic morphology, especially through inductive methods, enhances both linguistic understanding and spiritual engagement. Future studies should explore other derived noun forms across different surahs using similar models.